An analysis of the prevalence of osteoporosis and osteopenia in patients with epidermolysis bullosa: A cross‐sectional study. Issue 11 (10th January 2021) - Kang, Mina; Chen, Jessica S. C.; Radjenovic, Melissa; Yang, Anes; Feng, Grant H. Y.; Murrell, Dedee F.
Abstract: Background: Epidermolysis bullosa (EB) patients have multiple risk factors for osteoporosis. There is limited literature describing the prevalence of bone health in EB, particularly in adults and less severe EB types. Objectives: To investigate the prevalence of osteopenia or osteoporosis in EB patients from the Australasian Epidermolysis Bullosa Registry (AEBR). Methods: Of 417 AEBR patients, 72 underwent a dual energy X‐ray absorptiometry scan. Bone mineral density (BMD) T and Z‐scores, EB Disease Activity and Scarring Index (EBDASI), and Quality of Life in EB (QOLEB) scores were obtained. Results: T‐scores of RDEB patients were significantly lower than the diagnostic cut‐off value for osteopenia. EBDASI and QOLEB scores were inversely correlated with Z‐scores. The prevalence of osteoporosis in adults was 75% in severe EB types (RDEB and JEB). In adults with less severe types (EBS and DDEB), the prevalence of osteopenia was 50% and 33%, respectively. Conclusions: This is the largest study of osteoporosis in EB to date and the first to include adult patients with EBS. The high prevalence of osteoporosis and osteopenia identified in these patients warrants larger, collaborative international studies. Nevertheless, EB patients with high disease severity and QOL scores, irrespective of type, should receive early osteoporosis screening and prophylaxis.